Evaluation of the results of perioperative surgical robots in urology - literature review - Miszuda, Sławomir; Szwedkowicz, Agata; Trojan, Sara; Fussek-Styga, Urszula; Błaszczyk, Agnieszka; Kwieciński, Jakub; Basiaga, Bartosz; Bednarz, Krzysztof; Leśniak, Marek; Heluszka, Jakub (Quality in Sport, 2023)
Introduction: Operations with the use of surgical robots have become an acceptable method of treating urological complaints. The question remains what the perioperative results look like compared to other methods, such as classical surgery or laparoscopy. The aim of the study is to summarize the current state of knowledge about the use of surgical robots in urology, provide information on the types of procedures that can be performed with their help, safety and results Materials and methods: Literature review in databases: [Pubmed; science direct; google scholar]; searched using the words: [robotic surgery, surgical robots, BPH, robot, cystectomy, nephrectomy, retroperitoneal lymphadenectomy, prostatectomy,]. Publications from 2016 to 2023 were reviewed. Results: Data from multiple publications were collected. Promising perioperative results of surgical robots have been shown. Blood loss, length of hospital stay, and complication rate are lower compared to other methods. Positive surgical margins occur with a similar frequency. The safety of performing operations with the use of surgical robots in patients after previous chemotherapy or radiotherapy has been proven. The duration of the operation is usually longer compared to other methods. Conclusions: Performing surgery with the use of surgical robots is a promising method in urology. In many cases, perioperative outcomes are better. However, there is a lack of good quality studies conducted over a long period of time.